The Role of Organizational Ambidexterity in Product Quality - et. al., Haeder Jaleel Jabbar , (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The research aims to indicate the relationship between the main variables (Organizational Ambidexterity and product quality) of the research organization (Center Refineries Company) and to know that relationship, the research was applied to a sample of the research community (senior and middle management) of general managers and department managers and the research sample was (100) employees where the researcher used the descriptive-analytical method. The researcher used a questionnaire as a key tool in the process of collecting and analyzing the data obtained and specialized in research variables, where the research sample was tested through the assumptions of research and used several statistical means to show the relationship between the two variables of research (Organizational Ambidexterity and product quality) and to know the answers to questions raised at the intellectual and applied levels and to indicate the level of correlation and impact relationship and benefit from them by circulating the results to the research field (Center Refineries Company) The research reached a series of results, the most prominent of which was that the company exercises Organizational Ambidexterity at a high level and this indicates the strength of the link very high, as well as reached that the quality of the product was at a high level with the conclusion of a positive moral effect of statistical significance of the change of Organizational Ambidexterity in its dimensions on the quality of the product in the field of research. Through the results achieved, we show great interest from senior management in Organizational Ambidexterity and product quality.